MANAJEMEN LAYANAN PENDIDIKAN DI MADRASAH TSANAWIYAH GUPPI NATAR LAMPUNG SELATAN - ROBBY SANDI; DAMRAH KHAIR; ATIK RUSDIANI (UNISAN JURNAL, 2024)
This study aims to determine: (1) aspects of physical evidence (tangibles), (2) aspects of empathy (empathy), (3) aspects of reliability, at MTs Guppi Natar..The approach used in this research is qualitative research with descriptive analysis type. Data from each dimension of service quality in this study were collected through interviews, observation and documentation techniques. Research data were analyzed using triangulation techniques.The results of the study prove that: (1) The quality of services in the aspect of physical evidence (tangible) is the availability of facilities and infrastructure that support learning, but library and UKS facilities and prayer rooms are not yet available. MTs Guppi Natar. continues to provide health services and reading room facilities by utilizing unused classrooms. Meanwhile, to overcome the absence of a prayer room by carrying out prayer practices in the classroom. (2) Quality of service aspect of empathy (emphaty) is shown by the concern for service users in this case students, the attention to students who have ability levels below average. Keywords: Educational Service Management, Educational Services, Customer Satisfaction